Onset of Symptom Relief Reported in Daily Diaries of Patients With Atopic Dermatitis Treated With Baricitinib in a United States Clinical Trial (BREEZE-AD5). Issue 3 (May 2022) - Rosmarin, David; Casillas, Marta; Chen, Sherry; Dawson, Zach; Pierce, Evangeline; Zhang, Hong; Bukhalo, Michael; Smith, Stacy
Background: Itch and sleep disturbance due to itch are burdensome symptoms associated with atopic dermatitis (AD). Rapid onset of action is important for AD treatments to improve quality of life and relieve suffering. Objectives: This subanalysis evaluated how quickly baricitinib 1-mg and 2-mg reduced itch and associated sleep disturbance during the first 7 days after treatment initiation in a phase 3, double-blind, placebo-controlled trial. Methods: Adult patients with AD were randomized 1:1:1 to placebo ( N = 147), baricitinib 1 mg ( N = 147) or baricitinib 2 mg ( N = 146). Patients kept daily diaries, completing the Itch Numeric Rating Scale (NRS) (itch severity from 0 = no itch to 10 = worst itch imaginable) and the Atopic Dermatitis Sleep Scale (ADSS) to measure sleep disturbance (number of nighttime awakenings because of itch). Mixed model repeated measures analysis was used to analyze change from day 1 to day 7 values. Results: Patients receiving either dose of baricitinib had a 9.9% decrease in itch NRS scores from baseline to Day 2 vs 1.5% decrease for placebo (significant between-group least squares mean [LSM] difference: 8.3; 95% CI −12.66 to −3.89; P = .0002). Baricitinib 2 mg reduced nighttime awakenings due to itch (ADSS item 2) at day 2 by 25.2% vs 3.9% in the placebo group (between-group LSM difference: −21.4, P = .0025). Baricitinib 2 mg continued to demonstrate a statistically significant difference from placebo in sleep symptoms at day 7 (LSM difference −23.9; P = .001). Conclusions: Baricitinib 2-mg provided relief from itching and sleep disturbance in patients with AD, beginning the day after taking first dose. Clinical trials at www.clinicaltrials.gov: BREEZE-AD5 (NCT03435081)